Dissolution migration of gas, a mechanism to enrich ethane near the BSR and increase upwardly C1/C2 ratios in the hydrate-occurring zones: Insight from pore-scale experimental observation - Li, Hui; Lu, Xuekang; Wang, Lin; Wang, Wenjing; Li, Tianhua; Lu, Wanjun; Chen, Yong (Frontiers in Marine Science, 2023)
Most experiments show that gas hydrates are often enriched in C2+ gases relative to the feeding gas source because of fractionation during hydrate crystallization directly from free gases and dissolved gases. However, sediments below and near the base of the gas hydrate stability zone (BGHSZ) in many ocean drilling program (ODP)/International Ocean Discovery Program (IODP) sites are relatively enriched in C2+ hydrocarbon gases, compared with the hydrate-occurring zone above. It is still unclear what kind of process causes the abrupt decreases in C1/C2+ ratios with the depth in headspace gas in sediments around seismic bottom-simulating reflector (BSR) and increasing upward C1/C2 ratios in the hydrate-occurring zone. To test the “dissolution/migration mechanism” and its links to the enrichment of ethane near the BSR and increasing upward C1/C2 ratios in the hydrate-occurring zone, we performed a series of pore-scale experimental observations, simulating the gas dissolution–migration–hydration processes, and investigated the effects of the composition of feeding gases and temperatures on the composition of the hydrate grown under the dissolution–migration mechanism. Hydrates are grown from aqueous fluids supplied by the migration of gases dissolved from the capillary-trapped free gas in a capillary high-pressure optical cell, with different supplying gases (90 mol% CH4 + 10 mol% C2H6, 80 mol% CH4 + 20 mol% C2H6) and a geothermal gradient (temperature from 278.15 to 293.15 K). The gas hydrate structure and composition were determined by quantitative Raman spectroscopy. Our study indicated that (1) under the dissolution–migration–hydration processes, the mole fraction of C2H6 in hydrates is depleted compared with gas sources, which confirms that the dissolution–migration of gases is a mechanism to enrich ethane near the BSR; (2) the proportion of C2H6 in structure I (sI) or structure II (sII) hydrates decreases with decreasing temperature, and decreasing temperature enlarges the difference of diffusion coefficient between methane and ethane and enhances the gas fractionation during migration, which could cause the increase upwardly C1/C2 ratios in the hydrate-occurring zone. A simplified geological model was proposed to explain the variability of hydrate composition with depth in the hydrate-occurring zone and the fractionation of gases near the BSR.